Diary from the Kovno Ghetto : August 1942-January 1943 - Gerber, Ilya (2021)
""People lived, they had dreams, they wanted to live and to let others live, until... until suddenly they were exterminated before their time, because they wanted to eat, because they wanted to live, because they wanted to survive...;" Ilya Gerber was born in Kovno to an enlightened, Zionist family, and was seventeen years old when the Kovno Ghetto was sealed off in 1941. Gerber had kept a diary from mid-1941 to early 1943, but sadly, only part of it has been found. Published here for the first time, his diary reveals an intelligent and sensitive young man with a love of music, books, art, poetry–and a passion for writing. His story is of someone deeply immersed in ghetto life and aware of the consuming murderous reality, while still fiercely clinging to life. Gerber's description of daily ghetto life illuminates previously unknown facets of Jewish society and how it contended with a reality of oppression and persecution. He also depicts the lives and personal relationships of his family and friends, and various responses toward the challenging circumstances. Gerber accompanies his writing with many artistic illustrations. Ilya Gerber was tragically killed on April 28, 1945, during a march from the Dachau concentration camp to Wolfsratshausen in Germany. In his deeply sensitive, artistic, and sometimes humorous manner, Gerber's diary movingly portrays the broader story of Lithuanian Jewry during the Holocaust, particularly of the Jews of Kovno. Diary from the Kovno Ghetto: August 1942-January 1943 is an authentic and multifaceted historical document that gives voice to the thousands of young people interned in ghettos throughout Eastern Europe, and to the many victims of the Holocaust who did not record their own chronicles, or whose own accounts have been lost forever." – back cover